Political visions : George Russell, 1913-1930 - Allen, Nicholas George (Trinity College (Dublin, Ireland). School of English, 2000)
George Russell, poet and author, was a contemporary of W. B. Yeats and a figure central to the Irish Literary Revival. My thesis concentrates on his editorship of two journals, the Irish Homestead and the Irish Statesman, in the turbulent period between 1913 and 1930. I argue that Russell’s journalism enjoyed a cultural agency previously under-acknowledged by critics. Russell is now perceived to have been an eccentric, with mystical interests subsidiary to the main course of Irish nationalism. I contend rather that Russell was the central theorist of an Irish cultural doctrine subsequently obscured by post-Civil War political change. Russell's periodical contributions were expressions of his commitment to an esoteric principle of Irish statehood, anathema to an increasingly orthodox Free State.
Keywords: English Language and Literature, Ph.D.; Ph.D. Trinity College Dublin